ANALISIS YURIDIS PENYELENGGARAAN MEDIASI MENURUT HUKUM POSITIF DI INDONESIA - Heriyanti, Yuli; Zikri, Ahmad (Jurnal Pahlawan, 2024)
The court's authority to resolve civil disputes is based on the Trias Politika doctrine, giving rise to the stigma that the court is "the first and last resort" in resolving all disputes in society. Mediation is an alternative dispute resolution that is increasingly being prioritized in the Indonesian justice system, with the aim of reducing the burden on the courts and providing faster and more effective solutions for the parties to the dispute. This research uses a normative juridical method with a descriptive analytical approach. The data used is secondary data consisting of primary, secondary and tertiary legal materials. The formulation of the problem in this research is how to analyze the juridical implementation of mediation according to positive law in Indonesia. The research results show that Positive Law in Indonesia has regulations regarding the implementation of mediation to resolve disputes. This rule is expected to increase the effectiveness and efficiency of the mediation process in court. This research is normative juridical research with a legislative and analytical descriptive approach. The research results show that positive law in Indonesia regulates the implementation of mediation in resolving disputes, which has a significant impact on resolving cases that go to court and reducing prolonged conflicts between the parties. The principles of agreement between the parties determine the success of mediation. Keywords: Judical Analysis, Mediation, Positive Law.